THE DETERMINATION OF COLLAGEN METABOLISM IN SALIVA FOR THE CHILDREN WITH DYSPLASTIC SCOLIOSIS - Коротич, Н.М. (World of Medicine and Biology, 2016)
The saliva investigation of collagen metabolism carried out in 11-12 years old 50 children with dysplastic scoliosis and 25 personas with same age in control group. The significant increase of the hydroxyproline saliva excretion in 1.5-2 times was attested about increasing collagen disintegration in patients with dysplastic scoliosis in comparison with healthy children. The collagen catabolism increased and depended on the severity of the base disease.The children with caries and gingivitis have increasing level of collagen saliva elimination. The ascorbic acid deficiency detected in 59,42 ± 4,18% of children with scoliosis that was especially pronounced in 91,89 ± 4,49% children with scoliosis II degree severity and it’s a leading cause of collagen synthesis disruption and formation of onnective tissue. The children with scoliosis have undersaturation of ascorbic acid (hypovitaminosis C). These patients have the high percentage prevalence of caries and gingivitis on the background of hypovitaminosis C therefore it’s necessary to prescribe vitamin C in complex of preventive and treatment measures for these children.
Keywords: dysplastic scoliosis; hydroxyproline; ascorbic acid; caries; gingivitis; children